Autophagy as a Target for Drug Development Of Skin Infection Caused by Mycobacteria - Bittencourt, Tamiris Lameira; da Silva Prata, Rhana Berto; de Andrade Silva, Bruno Jorge; de Mattos Barbosa, Mayara Garcia; Dalcolmo, Margareth Pretti; Pinheiro, Roberta Olmo (Frontiers in Immunology, 2021)
Pathogenic mycobacteria species may subvert the innate immune mechanisms and can modulate the activation of cells that cause disease in the skin. Cutaneous mycobacterial infection may present different clinical presentations and it is associated with stigma, deformity, and disability. The understanding of the immunopathogenic mechanisms related to mycobacterial infection in human skin is of pivotal importance to identify targets for new therapeutic strategies. The occurrence of reactional episodes and relapse in leprosy patients, the emergence of resistant mycobacteria strains, and the absence of effective drugs to treat mycobacterial cutaneous infection increased the interest in the development of therapies based on repurposed drugs against mycobacteria. The mechanism of action of many of these therapies evaluated is linked to the activation of autophagy. Autophagy is an evolutionary conserved lysosomal degradation pathway that has been associated with the control of the mycobacterial bacillary load. Here, we review the role of autophagy in the pathogenesis of cutaneous mycobacterial infection and discuss the perspectives of autophagy as a target for drug development and repurposing against cutaneous mycobacterial infection.